What Causes a Management Article to be Cited—Article, Author, or Journal? - Judge, Timothy A.; Cable, Daniel M.; Colbert, Amy E.; Rynes, Sara L. (Academy of Management Journal, 2007)
This article examines the influence of citation impact on scholarship. Citation analysis allows authors to determine how often their work has been cited by others. It has become a performance metric for scholars of the influence and relevance of their work. However, the authors contends there is very little research to understand citation rates. They conclude that the pressure from journals and universities for prestige is the key element driving citation rates. Increased information technology is expected to continue this trend into the future.